National Youth Survey (United States): Wave VI, 1983 - Elliott, Delbert S. ([Verlag nicht ermittelbar], 1993)
Youth data for the sixth wave of the National Youth Survey are contained in this collection. This research project, which was designed to gain a better understanding of both conventional and deviant types of behavior by youths, involved collecting information from a representative sample of young people in the United States. The first wave of this survey was conducted in 1976 (ICPSR 8375), the second wave in 1977 (ICPSR 8424), the third wave in 1978 (ICPSR 8506), the fourth wave in 1979 (ICPSR 8917), and the fifth wave in 1980 (ICPSR 9112). For this wave, youths and young adults were interviewed in early 1984 about events and behavior occurring in calendar year 1983, when they were 17 to 26 years of age. Data are available on the demographic and socioeconomic status of respondents, disruptive events for parents, neighborhood problems, employment, children, aspirations and current successes, normlessness, labeling by parents, perceived disapproval by parents, peers, co-workers, and partner, attitudes toward deviance, exposure to delinquent peers, self-reported delinquency, drug and alcohol use, victimization, pregnancy, depression, use of outpatient services, spouse violence by respondent and partner, and sexual activity.